Electronic Dictionaries viewed from South Africa - Prinsloo, Danie J. (HERMES - Journal of Language and Communication in Business, 2005)
The aim of this article is to evaluate currently available electronic dictionaries from a South African perspective for the eleven ofﬁcial languages of South Africa namely English, Afrikaans and the nine Bantu languages Zulu, Xhosa, Swazi, Ndebele, Northern Sotho, Southern Sotho, Tswana, Tsonga and Venda. A brief discussion of the needs and status quo for English and Afrikaans will be followed by a more detailed discussion of the unique nature and consequent electronic dictionary requirements of the Bantu languages. In the latter category the focus will be on problematic aspects of lemmatisation which can only be solved in the electronic dictionary dimension.